2020
DOI: 10.1177/1010539520974848
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Prediabetes and Diabetes Among Public Employees in Northern Ethiopia

Abstract: The increasing burden of diabetes mellitus is one of the major public health challenges in African countries, including Ethiopia. This is the first study aimed to identify factors associated with prediabetes and diabetes defined by both fasting blood glucose and glycated hemoglobin in Ethiopians. We analyzed data of a cross-sectional survey (1372 adults aged 25-64 years) conducted between October 2015 and February 2016; multinomial logistic regression models were applied. Abdominal obesity, total cholesterol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
1
Order By: Relevance
“…We are not aware of any national studies in the country, which have reported on the prevalence of prediabetes/ diabetes. However, two recent studies in the North of Ethiopia observed prevalence rates of prediabetes, which were ~1.5-4 times higher than in our study (Endris et al, 2019;He et al, 2020). Reasons for this discrepancy could relate to the criteria used to classify prediabetes, differences in the sociodemographic profiles of the samples, and thus differential exposure to prediabetes risk factors or, given the recency of the studies, may reflect real increases in the burden of prediabetes in more recent years.…”
Section: Interpretation Of Findingscontrasting
confidence: 91%
“…We are not aware of any national studies in the country, which have reported on the prevalence of prediabetes/ diabetes. However, two recent studies in the North of Ethiopia observed prevalence rates of prediabetes, which were ~1.5-4 times higher than in our study (Endris et al, 2019;He et al, 2020). Reasons for this discrepancy could relate to the criteria used to classify prediabetes, differences in the sociodemographic profiles of the samples, and thus differential exposure to prediabetes risk factors or, given the recency of the studies, may reflect real increases in the burden of prediabetes in more recent years.…”
Section: Interpretation Of Findingscontrasting
confidence: 91%